Sociological Aspects of the Concept of Perception in Social Systems Theory - Lewkow, Lionel (MAD, 2014)
The aim of this article is to reconstruct and draft a concept of perception in the frame of Niklas Luhmann´s theory. Thus, we maintain that even when this concept refers to the operations of psychic systems, it shows important sociological aspects that were darken due to the relevance of the communication notion in the social systems theory. Defining the time of perception as simultaneity, its spatiality founded on the meaningful corporeality and the function of perception as the externalization of a world, we show the social derivations of perception, i.e., the link between social systems and psychic systems, the sociality of reciprocal perception and finally the meaning of perception in the context of science and love.